1997
DOI: 10.1139/f97-163
|View full text |Cite
|
Sign up to set email alerts
|

N and P limitation of benthos abundance in the Nechako River, British Columbia

Abstract: Abstract:Additions of inorganic N and P to replicated stream mesocosms were used to test the hypothesis that production of the benthic food web in the flow-controlled Nechako River, B.C., was N and P limited. N, P, and N + P additions were contrasted with controls to determine the responses of periphyton and macroinvertebrates over a 33-day period in late spring. Periphyton accrual under N + P addition was greater than two times that of the controls, and N alone produced a moderate increase. Periphyton showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 29 publications
3
24
0
3
Order By: Relevance
“…Here, lab experiments, small in situ exposure experiments, and large-scale observational studies afforded strong inference about the levels of heavy metals that affected biota in Rocky Mountain streams. Similar examples also exist for nutrients (e.g., Hart and Robinson 1990;Perrin and Richardson 1997;Lemly and King 2000). Thus, it seems that experiments can be a practical addition to the criteria development process if efficiently and purposefully designed.…”
Section: Discussionmentioning
confidence: 83%
“…Here, lab experiments, small in situ exposure experiments, and large-scale observational studies afforded strong inference about the levels of heavy metals that affected biota in Rocky Mountain streams. Similar examples also exist for nutrients (e.g., Hart and Robinson 1990;Perrin and Richardson 1997;Lemly and King 2000). Thus, it seems that experiments can be a practical addition to the criteria development process if efficiently and purposefully designed.…”
Section: Discussionmentioning
confidence: 83%
“…Benstead et al (2005) found that invertebrate abundance was 4 to 7× greater in an oligotrophic stream ecosystem after the addition of N and P and suggested that these changes were a result of enhanced food resources. Perrin and Richardson (1997) found that N and P additions to mesocosms increased mean invertebrate density by 70% over a period of 33 d and attributed their results to an increase in epilithic algal production.…”
Section: Invertebrate Densitymentioning
confidence: 98%
“…Enrichment of the Nechako River in British Columbia indicated N limitation (Perrin and Richardson 1997). Enrichment of a tundra river with P for four consecutive summers first stimulated algal biomass and productivity and eventually stimulated fish production (Peterson et al 1993).…”
Section: Defining Trophic State and Eutrophication In Streamsmentioning
confidence: 99%